2018
DOI: 10.1080/02713683.2018.1481517
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin Protects Human Retinal Pigment Epithelial Cells from Lipopolysaccharide-induced Inflammation and Cell Death

Abstract: These results suggest that esculetin may be an alternative treatment option for endotoxin-induced inflammation and oxidative stress, which therefore may inhibit the development of LPS-mediated AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…In addition to this, the NF-κB transcription level was partially decreased in the AlCl 3 + ESC group compared to the AlCl 3 group. It has been reported in another previous study that ESC has an anti-inflammatory effect partially by reducing NF-κB expression, which supports the results obtained in this study (Ozal et al, 2018). TNF-α initiates the cascade that enables the activation of some cytokines involved in inflammation (Kuzu et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to this, the NF-κB transcription level was partially decreased in the AlCl 3 + ESC group compared to the AlCl 3 group. It has been reported in another previous study that ESC has an anti-inflammatory effect partially by reducing NF-κB expression, which supports the results obtained in this study (Ozal et al, 2018). TNF-α initiates the cascade that enables the activation of some cytokines involved in inflammation (Kuzu et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…While previous studies have reported the potential roles of MAPKs in RPE cells treated with different stimulants and inhibitors, the results are inconsistent [39,40,41,42]. To explore the importance of three separate MAPKs in retinal inflammatory diseases, ARPE-19 cells were pretreated with MAPK inhibitors (10 µM p38 inhibitor SB202190, 10 µM ERK1/2 inhibitor U0126 or 10 µM JNK inhibitor SP600125) for 1 h prior to incubation with 1 ng/mL IL-1β for 24 h. Interestingly, the MAPK inhibitors reduced the IL-1β-induced expression of sICAM-1 but not that for ICAM-1 and ICAM-1 mRNA levels (Figure 6A,B and Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Some animals and microorganisms produce coumarin compounds [ 38 ]. Coumarins possess antioxidative activity [ 39 , 40 ] and esculetin is a well-established antioxidant [ 41 , 42 , 43 ]. Previous studies demonstrated that esculetin could bind to cytoplasmic Kelch-like ECH associated protein 1 (Keap1) to promote the nuclear translocation of Nrf2 in pancreatic cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%